Determinants of Telemedicine Adoption by Physicians in Developing Countries: A Conceptual Model Based on Systematic Review - Abdelaziz Zitouni; Oumaima Hafide; Yacoutt zenjali; Youness Lafraxo (Communications of International Proceedings, 2021)
Background: All over the world, the development of telemedicine is generating a lot of hope among public authorities, both in terms of improving access to care and controlling health costs. However, despite the great promise of telemedicine, its adoption and dissemination in developing countries is slow and poses complex problems. It is not always the technological factor that poses a problem, but above all the acceptance of this technology by physicians that conditions its deployment. However, the key factors behind the technology acceptance in developing countries are not clearly identified. Objectives: This research aims to propose a research model to predict the determinants of the adoption of telemedicine technologies by physicians in developing countries. Methods: to propose a research model to predict the factors of the adoption of telemedicine technologies by physicians in developing countries, a systematic literature review was conducted using the PRISMA-P (Preferred reporting items for systematic reviews and meta-analyses) methodology. Articles published between January 2010 and December 2020 that studied the determinants of telemedicine adoption and acceptance by physicians in developing countries were identified using three online databases: ScienceDirect, PubMed and Sage journals. The selection process excluded duplicate articles and thoses that did not directly address the objectives of this study. At the end, 12 articles were included. The extraction of results was done by two researchers, independently. Results: This study included 12 articles that examined the determinants of adoption and acceptance of Telemedicine use by physicians in developing countries. From these articles, 26 factors were identified and grouped into 4 classes: (1) environmental factors (2) individual characteristics of healthcare professionals, (3) organizational and managerial characteristics and (4) financial factors. Conclusion: Identifying the determinants of Telemedicine adoption in developing countries is crucial for health system managers and policy makers. It allows them to grasp the expectations of potential users and to adjust Telemedicine deployment strategies in order to successfully integrate the Telemedicine into medical practices.
Keywords: Telemedicine adoption; physicians; developing countries.